Teaching English for Academic Purposes: Exploring Rhetorical Strategies of Interactive Metadiscourse in the Introduction of Scopus-Indexed Research Articles - Mobit Mobit; Eri Kurniawan; R. Dian Dia-an Muniroh (Balai Bahasa Provinsi Bali, 2025)
This study aims to investigate rhetorical strategies for employing interactive meta-discourse aspects in the introductions of highly cited Scopus-indexed research publications from two separate academic fields: applied linguistics and electrical engineering. The study analyzed thirty Scopus-indexed journal articles from each of the two fields. To achieve the research purpose, the researchers employ a descriptive quantitative design with comparative corpus analysis. This research used Hyland's (2005) taxonomy, which consists of five subtypes of interactive metadiscourse: transition markers, frame markers, endophoric markers, evidentials, and code glosses, as the theoretical analysis. The findings indicate that both disciplines employ these features to establish coherence and cohesion; notable disparities arise in their distribution and rhetorical roles. Applied linguistics articles demonstrate a greater utilization of evidential and coding glosses, indicative of their narrative and intertextual focus. In contrast, articles on electrical engineering prominently utilize transition and endophoric markers, which signify a procedural and experimental methodology. This study illustrates the importance of genre awareness and epistemic tradition in academic writing instruction across several fields. AbstrakPenelitian ini bertujuan untuk meneliti strategi retoris dalam menggunakan meta-wacana interaktif pada bagian pendahuluan artikel jurnal yang terindeks Scopus yang bersitasi tinggi di bidang linguistik terapan dan teknik elektro. Studi ini menganalisis tiga puluh artikel jurnal terindeks Scopus dari setiap bidang. Untuk mencapai tujuan penelitian, peneliti menggunakan desain kuantitatif deskriptif dengan menganalisis korpus secara komparatif. Penelitian ini menggunakan taksonomi Hyland (2005), yang terdiri dari lima subtipe metawacana interaktif: pemarkah transisi, pemarkah bingkai, pemarkah endoforik, pembuktian, dan gloss kode, sebagai pisau analisis. Temuan menunjukkan bahwa kedua disiplin ilmu tersebut menggunakan fitur ini untuk membangun koherensi dan kohesi secara bervariasi. Temuan perbedaan yang paling penting muncul dalam distribusi dan peran retoris mereka. Artikel linguistik terapan menunjukkan pemanfaatan yang lebih besar dari pemarkah pembuktian dan gloses kode, yang menunjukkan keduanya fokus terhadap naratif dan intertekstual mereka. Sementara itu, artikel teknik elektro secara mencolok menggunakan penanda transisi dan endoforik, yang menandakan metodologi prosedural dan eksperimental. Studi ini menggambarkan pentingnya kesadaran genre dan tradisi epistemik dalam pengajaran penulisan akademik di beberapa bidang.